Effect of Disinfectants on Sea Cucumber Juveniles (Holothuria scabra) in Farming Practices - Broom, Mohammed; Satheesh, Sathianeson; Al-Harbi , Mamdouh; H. Gabr , Mohamed (Journal of King Abdulaziz University: Marine Sciences, 2022)
The rapid development of the intensive sea cucumber industry poses the appearance of potential threats, which makes it necessary to develop safe concentrations of common disinfectants used in aquaculture for controlling pathogens or infestation of predators. In this study, the effect of dip immersion and prolonged exposure of disinfectants on sea cucumber was investigated in order to formulate the optimum treatment concentrations. Acetic acid, formalin-FTM, copper sulphate, methylene blue, trichlorfon, potassium permanganate and dechlorinated freshwater were used as disinfectants. The effects such as evisceration, skin lesion and mortality were determined during exposure and post-exposure. The 1-min dip immersion of all chemicals used in the study was safe for disinfectant treatments and did not show any negative impact on sea cucumbers. The effect of prolonged exposure varied based on chemical toxicity, chemical concentration, and duration of exposure. Sea cucumber was less sensitive to acetic acid and trichlorfon for prolonged treatment and tolerates a wide range of safe concentrations up to 100 mg l-1 for acetic acid and 4 mg l-1 for trichlorfon. Sea cucumber was more sensitive to prolonged exposure to formalin, copper sulphate and methylene blue which caused severe effects. The upper-level concentrations which considered safe and did not show significant effect were 1 mg l-1, 0.05 mg l-1 and 4 mg l-1 for formalin, copper sulphate and methylene blue respectively. Potassium permanganate at 2 mg l-1 was very toxic to the sea cucumber. Freshwater bath for 1 and 10 minutes considered safe treatments for sea cucumber and no negative impact was observed. The study concluded that short dip immersion is a potential treatment for sea cucumber and considered safe to control the external pathogens and predators. Prolonged treatment with freshwater, acetic acid and trichlorfon could also be positively considered for sea cucumber treatment due to low sensitivity. Even though some of the disinfectants used in this study were toxic, they can be used at lower concentrations.